G81(P) Safety of "single checker" patient group directives for selected medications during initial nurse assessment in the emergency department (ed). (27th April 2015) - Bird, C; Hartshorn, S; Sinclair, A
Abstract : Aims: Innovative ways to optimise ED patient flow, without sacrificing quality of care, are at a premium. 2 Within our own paediatric ED, it was observed that inefficiency occurred whenever a triage nurse had to leave the assessment room in order to find a colleague to check the dose of a Patient Group Directive (PGD), including those for simple, over-the-counter medications. Doubt has been cast on the efficacy of double checking in all but high risk medications. 2 We aimed to evaluate the safety of a "single checker" PGD process at triage for paracetamol (pain and fever), ibuprofen (pain and fever), oral rehydration salts (ORS) and topical 4% tetracaine gel (Ametop) to improve patient flow. Methods: Single-checker PGDs were devised for the medications and indications listed above, to be used exclusively within the triage/assessment area by nurses who had completed PGD competency training. The process change was approved by the Trust Drug and Therapeutics Committee, after assurance that robust safety nets were in place (including the production of weight/dose tables for paracetamol and ibuprofen which were displayed in the assessment room). At launch, a 3 month audit (August–October 2011) was conducted, in which all single checker PGDs were logged. Subsequently, the hospital incident reporting system was reviewed for any medication errors associated with PGDs from ED. Results: During the first 3 months of the use of single-checker PGDs, no errors in dose were identified. To date, no medication errors associated with ED PGDs have been identified within the hospital incident reporting system. Benchmarking data regarding the prevalence of this practice within EDs in the PERUKI network will be identified. Conclusion: There were no drug errors with single checking by protocol of simple emergency medications at triage, within one of the UK's busiest paediatric EDs. Further research is required to quantify the time and resources saved on the patient journey. References: Sinclair D. Emergency department overcrowding – implications for paediatric emergency medicine. Paediatrics Child Health 2007;12:491–494 David U. Double checking: does it work? Can J Hosp Pharm. 2003;53:167–169